The corrosion behaviors of multilayer diamond-like carbon coatings: influence of deposition periods and corrosive medium. Issue 34 (18th March 2016) - Cui, Mingjun; Pu, Jibin; Zhang, Guangan; Wang, Liping; Xue, Qunji
Abstract : Electrochemical measurements, salt spray test and immersion test were employed to investigate the influence of deposition periods and corrosive medium on the corrosion behaviors of silicon doped multilayer diamond-like carbon (DLC) coating. Abstract : Electrochemical measurements, salt spray tests and immersion tests were employed to investigate the influence of deposition periods and corrosive medium (NaCl, H2 SO4, HCl, NaOH) on the corrosion behaviors of silicon doped multilayer diamond-like carbon (DLC) coatings. The results showed that the corrosion resistance of the multilayer DLC coatings was significantly improved with the increase of deposition periods. Interestingly, the coating with the highest deposition periods provided good corrosion protection in neutral and acidic solutions while poor corrosion protection in alkaline and acidic chloride solutions.